The symbolic dimension of the family against the backdrop of political changes in selected films by Zhang Yimou and Chen Kaige (Językowe, literackie i kulturowe refleksje na temat jedności w różnorodności, 2023)
The article analyzes the themes of the films: To Live! (1994) directed by Zhang Yimou and Farewell My Concubine (1993) by Chen Kaige. The main theme of the article is the image of the family against the background of political changes, especially against the backdrop of the Great Cultural Revolution and Mao Zedong's destructive policy. The analysis of both films is preceded by an introduction, which outlines the film motifs of the so-called Fifth Generation.